2016
DOI: 10.1187/cbe.16-01-0024
|View full text |Cite
|
Sign up to set email alerts
|

Efforts at Broadening Participation in the Sciences: An Examination of the Mentoring Experiences of Students from Underrepresented Groups

Abstract: Diversifying the scientific enterprise entails understanding how students from underrepresented backgrounds experience mentored research. Qualitative data were collected from mentees enrolled at community colleges about their research experiences. The themes were compared with previously collected data from mentors associated with the program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
(32 reference statements)
1
21
0
Order By: Relevance
“…Gender and racial/ethnic disparities in science, technology, engineering, and mathematics (STEM) higher education (Mau, 2016) have led to the creation of many federally and privately funded undergraduate educational programs over the past three decades in the United States in an attempt to level the educational playing field and to plug the leaky STEM pipeline. Many of these intervention programs focus on providing research experiences, as these experiences have been shown to benefit students while increasing their retention in STEM fields (Lopatto, 2004, 2007; Lopatto and Tobias, 2010; Prunuske et al. , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Gender and racial/ethnic disparities in science, technology, engineering, and mathematics (STEM) higher education (Mau, 2016) have led to the creation of many federally and privately funded undergraduate educational programs over the past three decades in the United States in an attempt to level the educational playing field and to plug the leaky STEM pipeline. Many of these intervention programs focus on providing research experiences, as these experiences have been shown to benefit students while increasing their retention in STEM fields (Lopatto, 2004, 2007; Lopatto and Tobias, 2010; Prunuske et al. , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There may be a number of reasons why URM students often lack adequate support from mentors, such as students’ lack of confidence in reaching out to mentors, or mentors focusing only on those students deemed “rising stars” according to conventional metrics (like grade point average or prestige of undergraduate university; Bangera and Brownell, 2014 ). Recent initiatives have sought to extend mentors’ training to include professional development competencies ( Handelsman et al , 2005 ; Pfund et al ., 2013 , 2014 ; Prunuske et al , 2016 ). However, the fact that there has been little improvement in the proportion of URMs in faculty positions over the past few decades suggests a need for supplemental career support beyond what many mentors are equipped to provide due to a lack of time or training ( McGee et al ., 2012 ; Thakore et al , 2014 ; Williams et al ., 2016a ).…”
Section: Introductionmentioning
confidence: 99%
“…Underrepresented minorities are in a distinctive position to address health disparities research, since they may have a better understanding of barriers to participation in research and other programs (Sopher et al, 2015). Ethnic and racial minorities are underrepresented in the field of public health (Prunuske et al, 2016; Sopher et al, 2015). Over the past two years, the SPHSP has identified and trained scholars who represent diversity in race and ethnicity.…”
Section: Public Health: Diverse In Disciplines and Diverse In Its Reachmentioning
confidence: 99%
“…If students are to become prepared to participate in public health scholarship, they need mentors who model a strong focus on health threats and risks (Rimer, 2016). They also need and are willing to receive constructive feedback, to make adequate time commitments, to communicate clearly (Prunuske et al, 2016), to provide socio-emotional support, and to engage in culturally relevant dialogue through inspiring exchanges (Haeger et al, 2016). The quality of mentorship influences the development of both research and academic abilities (Haeger, 2016); productive mentoring relationships can also emerge when the mentor and mentee are similar in their cultural, socioeconomic, and ethnic backgrounds (Haeger et al, 2016).…”
Section: Student-mentor Relationshipsmentioning
confidence: 99%